The Effect of Job Satisfaction on Turnover Intention Through Organizational Commitment as a Mediation - Mohyi, Achmad (Asia Pacific Journal of Management and Education (APJME), 2021)
The purpose of this study is to describe turnover intention, job satisfaction, and organizational commitment of the employees and to investigate the effect of job satisfaction on turnover intention through organizational commitment as a mediating variable. The sample in this study was 56 employees of Sengkaling Recreation Park Malang selected by the saturated sampling technique. The analysis tool was a scale range analysis and path analysis. The findings indicate that job satisfaction has a negative effect on turnover intention, job satisfaction has a positive effect on organizational commitment, organizational commitment has a negative effect on turnover intention and job satisfaction has a negative effect on turnover intention through organizational commitment as a mediating variable. The Sobel test shows that organizational commitment is proven to be the mediating variable.